Combination of Effleurage Massage, Bitter Orange Aromatherapy and Beethoven Music as An Alternative Solution to Reduce Back Pain in Pregnant Women in the Third Trimester - Dianita Primihastuti; Sendy Firza Novilia Tono; Intiyaswati Intiyaswati (Indonesian Journal of Global Health Research, 2025)
Back pain is a common complaint in pregnant women during the third trimester due to physiological changes affecting the connective tissue and spinal structure. This study aimed to evaluate the effectiveness of a combination of effleurage massage, bitter orange aromatherapy, and Beethoven's music on reducing back pain and physiological responses in pregnant women during the third trimester. The study design used a quasi-experimental approach with a pre-post test control group approach. Sixty respondents were divided into two groups: the intervention and the control. The intervention group received the combination therapy three times a week for four weeks, while the control group received no intervention. The results showed a significant decrease in blood pressure, pulse rate, respiratory rate, and pain scores after the intervention. Most respondents in the intervention group experienced a shift in pain category from moderate and severe to mild pain. In contrast, the control group showed no significant changes. This combination therapy proved to be physiologically and psychologically effective, consistent with the gate control pain theory and supported by previous literature. The combination of touch through massage, the aroma of bitter orange oil, and classical music stimulation provided a comprehensive relaxation effect. This intervention is safe, non-invasive, and easy to implement both independently and in midwifery practice. Therefore, this combination therapy is recommended as a complementary approach in antenatal care services to address back pain in pregnant women in the third trimester.